A Discourse Network Analysis: How are Freelancers in Indonesia Portrayed? - Arifianto, Chandra; Tajuddien, Rahadyan; Kustini, Endang; Putri, Syahrina (PT. Riset Press International, 2024)
This research focuses on the freelancer policy published in the electronic daily, Kompas, from 2003 to 2022 with a Discourse Network Analysis approach. This form of research includes qualitative research. The technique used for data collection is library research. The data analyzed is secondary data, namely in the form of online news articles on the Kompas.com portal. There are 98 pro and con statements. Data analysis using DNA Analyzer. It was obtained that the economic value of pro statements was 28 statements and there were 10 counter statements. In the autonomy value, there are 27 pro statements and 4 counter statements. The value of work-life balance has 18 pro statements and 1 counter statement. There are 4 social values ​​for pro statements and 3 counter statements. There are 6 pro statement development values ​​and 1 counter statement, then visualized using the Visone application. The research results show that there are six value propositions for daily freelancers, there is only one value that is not discussed, namely hedonic value. Regarding economic value, the focus of the discussion focuses on holiday allowances for freelancers. Meanwhile, the autonomy value discussed is freelancers who have no bargaining value. In terms of social values, discussions on the recruitment of freelancers still experience many obstacles, thus triggering conflict. Next, the balance value discusses daily freelancers who are forced to work outside company working hours. Lastly, the development value discusses the large number of daily freelancers in Indonesia.